Gender, education, eating patterns, and nutritional status among high school students in the tourist area of Bukittinggi, Indonesia - Taufiqa, Zuhrah; Maisa, Benny Alexander; Zam, Zelly Salmiyanti Rahman; Ranza, Fathiya Rizqillah; Alem, Najla Khalisha; Amril, Farah Alya (Indonesian Nutrition Association, 2025)
Background: The well-being of high school students in tourist shapes their eating habits and affects their nutritional status, leading to obesity and malnutrition. Objective: This study aims to examine the association between gender, education, eating patterns, and nutritional status among high school students in tourism areas. Methods: This cross-sectional study was conducted in October 2023 and included 118 students aged 12–18 years from junior and senior high schools in Bukittinggi, West Sumatra. Respondents were selected through multistage stratified clustered sampling. Data on gender, age, education, and eating patterns which assessed using a food frequency questionnaire classified according to the Guttman scale. Nutritional status was determined based on BMI-for-age WHO z-scores following the Indonesian Minister of Health Regulation. Data were collected via interviews using a questionnaire on the KoboToolbox application and analyzed using Chi-square tests. Results: Most high school students (89.8%) had poor eating patterns, with 45.8% having a normal BMI-for-age, 34.7% undernourished, and 19.5% overweight or obese. Gender was significantly associated with nutritional status (p=0.007), with thinness more common in boys and normal BMI-for-age more prevalent in girls, while education and eating patterns showed no significant association. However, frequent consumption of sugary drinks was linked to higher rates of overweight and obesity. Conclusion: There were gender differences in nutritional status among high school students in Bukittinggi, a tourist area, underscoring the need for targeted gender-focused nutrition interventions to address healthier eating patterns in tourism regions.